Implementasi Expert System Diagnosa Penyakit Hipertensi Menggunakan Metode Dempster Shafer - Renanda Eka Putri; Iqbal Kamil Siregar; Elly Rahayu (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Currently the development of the world of technology is growing rapidly, especially in the world of IT (Informatic Technology). One aspect that is affected by the development of the IT world is the world of health, especially in the medical field. One of the uses of Information Technology in the medical field is the use of expert systems in facilitating the analysis of a disease. The author designed an expert system application that aims to be able to make a diagnosis of hypertension. This application is a web-based expert system application so that it can be accessed by users wherever and whenever they are. The inference process in this system using the Dempster Shafer method is a representation, combination and propagation of uncertainty, where this theory has several characteristics that are intuitively in accordance with the way of thinking of an expert, but have a strong mathematical basis. In this theory can distinguish uncertainty and ignorance. With this application a person can quickly find out the possibility of the disease he is suffering from, so that he can immediately take quick action. Keywords— Expert System, Dempster Shafer, hypertension disease